From Dialogue to Digital Spiritual Practice: Thematic Content Analysis of "Tiga Fakir" on YouTube - Hilma Pami Putri; Zikrawahyuni Maiza; Merry Prima Dewi (Jurnal Fuaduna : Jurnal Kajian Keagamaan dan Kemasyarakatan, 2025)
This study aims to examine how dialogic, non-clerical digital discourse can be transformed into everyday spiritual practice within contemporary online religious ecosystems. Focusing on the “Tiga Fakir” segment on the SAY Inspiratif YouTube channel, the research addresses a critical gap in digital religion studies, where spiritual communication is often dominated by one-way preaching rather than participatory dialogue. Employing thematic content analysis, the study analyzes cleaned transcripts of the episode “Menjawab Pertanyaan Abadi Dalam Kehidupan” alongside audience reception data drawn from YouTube comments. The analysis identifies five mechanisms through which dialogue is converted into practice: (1) the framing of the “aku satu, aku dua, aku tiga, dan aku empat” scheme as a practical compass for everyday decision-making; (2) dialogic speech acts that normalize confusion and employ humor to lower participation barriers; (3) a non-clerical ethos that enhances spiritual self-efficacy through invitations to “small starts”; (4) narrative performativity that stabilizes shared terminology into repeatable micro-routines; and (5) platform affordances that enable participatory hermeneutics among audiences. The findings demonstrate that audience engagement exceeds affective resonance, functioning instead as a site of peer clarification and explicit adoption of spiritual practices. The study concludes that the “Tiga Fakir” dialogue operates as an operational map of digital spirituality, illustrating how complex frameworks of self and consciousness can be translated into transformative, everyday disciplines through dialogic media practices.